Analysis of the Company's Financial Statements with a Financial Ratio Approach: Case Study of PT Indofood Sukses Makmur Tbk. - Sabda Dian Nuraini Siahaan; Via Yusnika Suhendy; Rehulina Dahinta Ketaren; Artha Rehwelda Lumban Gaol; Abdillah Rizky Ananta Lubis (Asian Journal of Management Analytics, 2023)
The purpose of this research is to conduct an in-depth analysis of the financial statements of the company PT Indofood Sukses Makmur Tbk by using financial ratios as an approach. The method used in this research is the descriptive statistical method, which uses liquidity, solvency, activity, and profitability ratios from 2019 to 2022 as material for analyzing financial statements. The results of the study describe the calculation of each financial ratio of the company and how, in each ratio, the company's finances have increased or decreased. This shows that PT Indofood Sukses Makmur Tbk has been able to improve its financial ratios, even though they are still not stable.